Th2 cell-derived IL-4/IL-13 promote ILC2 accumulation in the lung by ILC2-intrinsic STAT6 signaling in mice - Symowski, Cornelia; Vöhringer, David (European Journal of Immunology, 2019)
Infection of mice with the gastrointestinal helminth Nippostrongylus brasiliensis elicits profound local proliferation and accumulation of type 2 innate lymphoid cells (ILC2s) in the lung. The regulation of ILC2 proliferation and accumulation in the lung is poorly understood. Using T cell-specific IL-4/IL-13-deficient mice, we demonstrate that IL-4/IL-13 secretion from Th2 cells promotes proliferation and expansion of the ILC2 population in the lung of N. brasiliensis-infected mice. Competitive mixed BM chimeras containing normal and STAT6-deficient ILC2s further indicated that ILC2s have to respond directly to IL-4/IL-13 for this effect while STAT6 is not required for IL-13 production in ILC2s. In addition, expression of a constitutively active form of STAT6 in ILC2s was sufficient to promote their proliferation in uninfected mice. The expression of MHC class II in ILC2s appeared to be enhanced by STAT6 signaling supporting the concept that Th2 cells and ILC2s can communicate in an antigen-dependent manner resulting in a Th2-regulated accumulation of ILC2s in the lung during an acute type 2 immune response. Based on our observations, targeting the STAT6 pathway in ILC2s could help to develop new treatments to dampen ILC2 proliferation in the lung and thereby ameliorate ILC2-mediated allergic inflammation.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Allergy; Asthma; Helminths; ILC2 homeostasis; Type 2 immunity